THE CAPABILITY OF SEDATIVE EFFECT FROM CELERY (Apium graveolens L.) FRACTION TO MALE MICE - Kusuma, Shinta; Setiawan, Arum; Salni, Salni (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2018)
Celery fraction research (Apium graveolens L.) was carried out to determine the ability of the sedation effect of celery fraction compared to celery extracts which have been known to have the ability to effect the previous sedation. This study aims to find out which fraction has the best sedation effect. This study was an experimental study with a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. Test animals divided into 5 treatment groups namely negative control group (CMC Na 1%), celery extract group 200mg /kg and 3 treatment groups n-hexane fraction, ethyl acetate, and methanol water fraction with a dose of 200 mg /kg . The sedation effect test was carried out using the Traction Test and Fireplace Testmethods. Quantitative data observed were the length of time the mice fell and the length of time the mice went out of the heated tube/glass. The results of the analysis showed that the celery fraction had a better sedation effect than the extract, and the methanol water fraction 200 mg/kg was the most effective fraction in causing sedation effects.